A Hit, a Hit—A Very Palpable Hit: Mild TBI and the Development of Epilepsy. Issue 4 (July 2019) - Danzer, Steve C.
Repetitive Diffuse Mild Traumatic Brain Injury Causes An Atypical Astrocyte Response and Spontaneous Recurrent Seizures Shandra O, Winemiller AR, Heithoff BP, et al. J Neurosci . 2019;39(10):1944-1963. doi:10.1523/JNEUROSCI.1067-18.2018. Epub 2019 Jan 21. PMID:30665946 . Focal traumatic brain injury (TBI) induces astrogliosis, a process essential to protecting uninjured brain areas from secondary damage. However, astrogliosis can cause loss of astrocyte homeostatic functions and possibly contributes to comorbidities such as posttraumatic epilepsy (PTE). Scar-forming astrocytes seal focal injuries off from healthy brain tissue. It is these glial scars that are associated with epilepsy originating in the cerebral cortex and hippocampus. However, the vast majority of human TBIs also present with diffuse brain injury caused by acceleration–deceleration forces leading to tissue shearing. The resulting diffuse tissue damage may be intrinsically different from focal lesions that would trigger glial scar formation. Here, we used mice of both sexes in a model of repetitive mild/concussive closed-head TBI, which only induced diffuse injury, to test the hypothesis that astrocytes respond uniquely to diffuse TBI and that diffuse TBI is sufficient to cause PTE. Astrocytes did not form scars and classic astrogliosis characterized by upregulation of glial fibrillary acidic protein was limited. Surprisingly, an unrelated population of atypical reactive astrocytes was characterized by the lack of glial fibrillary acidic protein expression, rapid and sustained downregulation of homeostatic proteins, and impaired astrocyte coupling. After a latency period, a subset of mice developed spontaneous recurrent seizures reminiscent of PTE in human patients with TBI. Seizing mice had larger areas of atypical astrocytes compared with nonseizing mice, suggesting that these atypical astrocytes might contribute to epileptogenesis after diffuse TBI. Traumatic brain injury is a leading cause of acquired epilepsies. Reactive astrocytes have long been associated with seizures and epilepsy in patients, particularly after focal/lesional brain injury. However, most TBIs also include nonfocal, diffuse injuries. Here, we showed that repetitive diffuse TBI is sufficient for the development of spontaneous recurrent seizures in a subset of mice. We identified an atypical response of astrocytes induced by diffuse TBI characterized by the rapid loss of homeostatic proteins and lack of astrocyte coupling while reactive astrocyte markers or glial scar formation was absent. Areas with atypical astrocytes were larger in animals that later developed seizures suggesting that this response may be one root cause of epileptogenesis after diffuse TBI.